Eco-friendly synthesis F Cadmium sulfide nanoparticles using supernatant of Bacillus badius and its characterization. (2021) - Sharma, Aman; Chaturvedi, Rishabh; Islam, Anas; Singh, Pankaj Kumar
Abstract: Development of reliable and eco friendly process for synthesis of nano particles is an important step in the field of nanotechnology. One of the options to achieve this objective is the use of natural factories such as biological systems. Supernatant of Bacillus badius organism is used for the reduction of Cadmium Sulphate to Cadmium Sulphide nano particle. The Cadmium Suphide nano particle have been confirmed through the UV–Visible spectra, which shows a characteristic absorption at 425 nm corresponding to the surface Plasmon absorbance of Cadmium Suphide nano particles. XRD data of the Cadmium Sulphide nano particles shows line broadening effect and the particle size evaluated using Scherrer equation. A fine distribution of nano particles is observed from the AFM image and the surface topography, Particles size etc is measured and found in the range of 40–80 nm. The process of reduction being extracellular and fast may lead to the development of an easy bioprocess for synthesis of Cadmium Sulphide nano particles.